Industrial training report: Bahagian Hal Ehwal Akademik (HEA) Universiti Teknologi MARA (Kelantan) / Wan Sahzwan Nadzmi Sukardi - Sukardi, Wan Sahzwan Nadzmi (Perpustakaan Tengku Anis, 2018)
The Farmers Organization Authority (LPP) was established on 14 February 1973 through the act of the LPP Act 1973 (Act 110). The creation of LPP is aimed to be to assuming responsibility for improving the economic and social status of the peasant community under a specific role. However in the local level it is called Areas Farmers Organization (PPK), every state in Malaysia for example Kelantan, Terengganu, Johor, Melaka and so forth received the services from each PPK at there state.